Kalimat Efektif dalam Teks Laporan Hasil Observasi Siswa Kelas X Sekolah Menengah Atas Negeri 1 Kecamatan Guguak Kabupaten Lima Puluh Kota - Safira Ratna Juita; Yulianti Rasyid (AHKAM, 2025)
The ability to write effective sentences in observational report texts remains a challenge for secondary school students, primarily due to limited understanding of sentence structure, diction selection, and application of the Enhanced Spelling System (Ejaan yang Disempurnakan, EYD). This study aims to describe the effectiveness of sentences in the observational report texts written by Grade X students at SMAN 1 Guguak, Lima Puluh Kota Regency. A qualitative approach with a descriptive method was used. The sample consisted of 25 student reports, from which 522 sentences were analyzed using a staged elicitation technique: reading and understanding the texts, inventorying data, and classifying forms of effective sentences. Data analysis involved coding, identifying sentence forms, discussing findings, and drawing conclusions, with validity ensured through detailed descriptions and direct excerpts from student texts. The results revealed that only 216 sentences (41.4%) were classified as effective, while 306 sentences (58.6%) were ineffective. The most common errors were related to sentence structure (111 cases), followed by spelling (100 cases), and diction (95 cases). These findings indicate a low level of student proficiency in writing sentences that adhere to formal language norms. The study concludes that explicit instruction on effective sentence construction should be integrated into writing activities to help students express ideas clearly, concisely, and in accordance with proper Indonesian language standards.